An assessment of the distribution and effects of Acanthaster planci (L) on the Great Barrier Reef. (Townsville, Australia AIMS, 1986)
Contents: 1. Methods; 2. Massive Coral Study; 3. Princess Charlotte Bay; 4. Cape Grenville; 5. Cooktown--Lizard Island; 6. Cairns; 7. Innisfail; 8. Townsville; 9. Cape Upstart; 10. Whitsundays; 11. Pompeys; Swain; 13. Capricorn--Bunker
Keywords: Crown-of-thorns starfish--Australia--Great Barrier Reef; Great Barrier Reef